Efficacy of postoperative radiation treatment for bone metastases in the extremities. Issue 1 (July 2017) - Drost, Leah; Ganesh, Vithusha; Wan, Bo Angela; Raman, Srinivas; Chan, Stephanie; Christakis, Monique; Tsao, May; Barnes, Elizabeth; Ford, Michael; Finkelstein, Joel; Yee, Albert; Turner, Angela; et al.
Abstract: Background and purpose: Impending or pathological fractures due to bone metastases may require surgical fixation. Postoperative radiation is often recommended to reduce local progression and prevent prosthesis displacement, hence reducing the need for second surgery. The objectives of this study were to investigate the need for second surgery, and to report on rates of re-irradiation, tumor progression and prosthesis displacement following postoperative radiation. Materials and methods: Data were collected from 65 patients who received postoperative radiation to 74 sites in the extremities in a palliative radiation clinic between January 2009 and January 2017. Descriptive statistical analyses were performed. Results: Only 2 patients required a second surgery (2.7%) at 9 and 10 months after postoperative radiation. Increase in pain requiring re-irradiation was reported in 7 patients (9.5%), at a median time of 9.3 months after the delivery of radiation. Of the 47 patients who had radiological imaging available post-radiation, local progression of bone metastases was seen in 8 patients (17.0%) and displacement of the prosthesis in 1 patient (2.1%). Conclusion: Rates of prosthesis displacement and progression of bone metastases at site of surgery were low after postoperative radiation. There were few incidences of second surgery and re-irradiation observed in the cohort. These findings provide support for the benefit of postoperative radiation.